NAVIGATING JUSTICE AND EFFECTIVENESS: PROGRESSIVE INSIGHTS INTO THE APPEAL RIGHTS OF DEFENDANTS IN CONFESSION-DRIVEN CASES - Costa , Julian (Ayden International Journal of Education and Social sciences, 2024)
The Chinese Criminal Procedure Law includes a no cause appeal system, providing comprehensive protection without requiring a review of the appellant's request. Current academic research primarily focuses on the abuse of appeal rights in cases involving confessions and punishments. The tension between the values of "fairness" and "efficiency" in the criminal litigation system intensifies when dealing with leniency systems for confessions, punishments, and appeal procedures, leading to significant debate in the academic community regarding limitations or prohibitions on the right to appeal. This article takes a materialist and dialectical perspective to balance the relationship between "fairness" and "efficiency" by expanding the theory supporting the right to appeal and distinguishing various theories. It aims to establish the necessary relationship between the right to appeal and the right to protest.